2007
DOI: 10.1021/ef7002409
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Based Ceria, Zirconia, and Ceria–Zirconia Catalytic Systems for Low-Temperature Carbon Dioxide Reforming of Methane

Abstract: Carbon dioxide reforming of methane (CDRM) was studied over a variety of ZrO 2 -, ceria-doped ZrO 2 -, and CeO 2 -ZrO 2 -supported Ni catalysts. Different techniques were used to prepare supports material having different physicochemical properties, and a correlation was established to show the importance of a robust support material. Various characterization of the catalyst further established that the coking behavior of the catalyst depends on the support preparation techniques. Compared to zirconia and ceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 26 publications
8
116
0
1
Order By: Relevance
“…Therefore, the observed shift in 2 positions is the outcome of successful substitution of Ce 4+ ions with isovalent Zr 4+ . This also confirms the formation of CZ solid solutions [22,23]. This incident is quite reinforced by the fact that CZ has smaller crystallite size than pure CeO 2 (obtained from Scherrer equation) as can be seen from the values given in Table 1 [7,24].…”
Section: Resultssupporting
confidence: 70%
“…Therefore, the observed shift in 2 positions is the outcome of successful substitution of Ce 4+ ions with isovalent Zr 4+ . This also confirms the formation of CZ solid solutions [22,23]. This incident is quite reinforced by the fact that CZ has smaller crystallite size than pure CeO 2 (obtained from Scherrer equation) as can be seen from the values given in Table 1 [7,24].…”
Section: Resultssupporting
confidence: 70%
“…In this respect, nickel based catalysts attract particular attention as they are known to exhibit excellent catalytic performance; the drawback is that they suffer from the aforementioned problems Charisiou et al, 2016b;Elsayed et al, 2017). In theory, coke deposition can be avoided by: (i) altering the electronic properties of metal-support interactions, (ii) influencing the size of metallic particles and, (iii) improving the oxygen storage capacity and mobility within supporting material (Roh et al, 2006;Kumar et al, 2007;Chen et al, 2008;Goula et al, 2014;Yentekakis et al, 2015Yentekakis et al, , 2016Han et al, 2017). Thus, the attempts that have been undertaken to improve the stability of DRM nickel catalysts have focused on the use of different oxides as supports (e.g., Al 2 O 3 , SiO 2 , La 2 O 3 , CeO 2 , ZrO 2 ) (Pompeo et al, 2007;Bereketidou and Goula, 2012;Li et al, 2016) or the use of a variety of dopants that include transition metals (e.g., Fe, Co, Sn) (Ay and Uner, 2015;Theofanidis et al, 2015;Zhao et al, 2016), noble metals (e.g., Ag, Pt, Pd, Ir) Yentekakis et al, 2015;Yu et al, 2015), lanthanide metals (e.g., La, Ce, Pr) (Goula et al, 2016a;Vasiliades et al, 2016;Xiang et al, 2016) and alkaline earth metals (e.g., Sr, Ca, Ba) (Bellido et al, 2009;Sutthiumporn and Kawi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study on a commercial MSR catalyst by Choi and Stenger has shown a good on stream reactivity pattern at a very low space velocity of 1100 h -1 [4]. In another study, Kumar et al have carried out the CO2 reforming reaction of CH4 over 5% Ni impregnated on surfactant (CTAB) assisted coprecipitation synthesized Ce0.60Zr0.40O2 showing better the catalytic stability than the corresponding normal coprecipitation prepared sample [39]. In other word, the catalytic activity of the materials is highly sensitive to the synthesis procedure adopted.…”
Section: Discussionmentioning
confidence: 92%
“…The latter method has drawn considerable interest due to the high surface area and Though the CO formation can take place either via reverse WGS reaction or via methanol decomposition, most studies have reported its formation exclusively through the former reaction [4,7e9]. Peppley et al suggested that the major improved thermal stability of the resulting materials [39].…”
Section: Introductionmentioning
confidence: 99%